Development of VVF following double J stent placement - Priyadarshi, Vinod (BMJ Publishing Group, 2014)
Double J stent (DJ stent) is commonly used in various urological conditions. Theoretically stent-induced tissue erosion can be a possibility, but fistula formation is rarely reported. The present case was a case of genitourinary tuberculosis diagnosed 4 years ago and had received complete treatment. Two months ago she presented with recurrent urinary tract infection and diagnosed to have vesicoureteric reflux with secondary obstruction for which DJ stent was placed, after 15 days of which the patient reported leakage of urine per vagina. She was diagnosed to have vesicovaginal fistula (VVF) with in situ stent eroding through the bladder wall. Stent was removed and fistula was corrected surgically. This is the first reported case of stent-induced VVF, a rare complication of ureteral stent placement.